Biglycan regulates bone development and regeneration - Shainer, Reut; Kram, Vardit; Kilts, Tina M.; Li, Li; Doyle, Andrew D.; Shainer, Inbal; Martin, Daniel; Simon, Carl G.; Zeng-Brouwers, Jinyang; Schaefer, Liliana; Young, Marian F.; , Genomics and Computational Biology Core (Frontiers in Physiology, 2023)
Endochondral bone development and regeneration relies on activation and proliferation of periosteum derived-cells (PDCs). Biglycan (Bgn), a small proteoglycan found in extracellular matrix, is known to be expressed in bone and cartilage, however little is known about its influence during bone development. Here we link Bgn with osteoblast maturation starting during embryonic development that later affects bone integrity and strength. Bgn gene deletion reduced the inflammatory response after fracture, leading to impaired periosteal expansion and callus formation. Using a novel 3D scaffold with PDCs, we found that Bgn could be important for the cartilage phase preceding bone formation. The absence of Bgn led to accelerated bone development with high levels of osteopontin, which appeared to be detrimental to the structural integrity of the bone. Collectively, our study identifies Bgn as an influencing factor in PDCs activation during bone development and bone regeneration after fracture.